Pengaruh Media Buku Berjendela terhadap Kemampuan Literasi Sains Peserta Didik Kelas V UPT SDN 064964 Medan Timur - Wulandari, Fadilah; Amini, Fatimah; Rizky, Seri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This reseach was conducted because the results of our obsevations saw that students could not understand the process of food travel in the human body as well as students who did not have an overview of the human digestive organs. This study aims to improve student learning outcomes on the material of the human digestive organs by using windowed book media so that students better understand how the process of food travels from the mouth to the esophagus. This study uses a quantitative approach and has various research methods, one of the research methods is the experimental method. The experimental method is able to bring up an experimental problem that can make students think critically and be able to develop scientific literacy.The results of this study indicate that the Window Book media on the function of the human digestive organs and their relationship to food and health meets valid and practical criteria, with an average score of 80% LKPD language validation or can be said to be good, the average expert validation results media with a score of 83% or very good and for the assessment of the post test score taken from the average value of 88.3 compared to the pree test of 31.25. Then the Windowed Book Media has met the valid criteria and can be used by teachers. Based on the research results obtained, the suggestions that can be given are: 1). For Teachers, the delivery of learning material is complemented by using interesting media, namely using Window Book learning media. 2). For schools, it can encourage teachers to be more creative in creating or providing learning media that are appropriate and support the learning process. One alternative learning media that can be used is the Window Book learning media. 3). For Researchers, Realizing that the research and development of this Window Book media are not yet perfect, other development research should be carried out in the future as a complement to this research and become a new product indevelopment research on natural science subjects and other subjects Keywords: Influence, Windowed Book, Media